Le verbe support complexe: un actualisateur figé de la prédication non verbale - Lajmi, Dhouha (Neophilologica, 2011)
Any linguistic unit is described in the theoretical and methodological frame of the laboratory LDI — Lexique, Dictionnaires, Informatique (Lexicon, Dictionaries, Computing) according to one of three primary functions, namely predicate, argument or actualizer. The description of the syntactic-semantic functioning of these lexical items will be undertaken with the aid of a corpus of free sequences and motionless sequences. In this article we look into a sample of complex support verbs considered as motionless actualizers of the nominal predicates.